PEMETAAN SEBARAN ENDAPAN NIKEL LATERIT DENGAN METODA RESISTIVITAS DI DAERAH GUNUNG TINGGI TALAGA PIRU, KABUPATEN SERAM BAGIAN BARAT PROVINSI MALUKU - , Sisca Madonna Sapulete, Prof. Dr. Sismanto, M.Si ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Geophysical research has been done by using resistivity method at Gunung Tinggi Talaga Piru, Western Seram Regency, Moluccas Province on September 26 till October 4, 2011. This research aims to find out the existence of lateritic nickel deposit and resource estimation of lateritic nickel deposit in the research area. The area is 110.000 m2 with a total of 7 lines of survey, whose spaces between the measurement points were 10 meters and the length of each line was 210 meters. The data were processed by using Res2Dinv software to generate information about the true resistivity in 2-D section. Then the data were analyzed and correlated to the results of petrography analysis, geochemical analysis, and geological surface data. Petrography analysis can determine the characteristic of minerals of rocks, geochemical analysis can determine the element contents of rocks, and geological surface data prove the informations about the existence of lateritic nickel and its resistivity value in the research area. Furthermore, the 3-D modeling was made using the Oasis montaj software ver 6.4.2 to estimate the volume of lateritic nickel deposit. The result of samples analysis indicate that the average total content of elements in all lines for Co, Fe, and Ni were 0,02%, 4,70%, and 1,29%. The value of lateritic nickel resistivity in this area ranged from 40-150 ohm meter for limonite zone and from 150-400 ohm meter for saprolite zone. From result of the 3-D combined sections of limonite and saprolite, it can be known that the measurable potential model for lateritic nickel was 326.673 m3, so the total of estimated lateritic nickel resources in the research area was 658.572,77 tons at the concentration of 1,29%. The measurable potential amount of lateritic nickel covers only the research area.